Crystallization and preliminary X-ray crystallographic analysis of chorismate synthase from Mycobacterium tuberculosis - Dias, MVB; Ely, F.; Canduri, F.; Pereira, J. F.; Basso, L. A.; Palma, Mario Sergio [UNESP]; de Azevedo, W. F.; Santos, D. S. (Blackwell Munksgaard, 2004)
The enzymes of the shikimate pathway are potential targets for the development of new therapies because they are essential for bacteria but absent from mammals. The last step in this pathway is performed by chorismate synthase (CS), which catalyzes the conversion of 5-enolpyruvylshikimate-3-phosphate to chorismate. Optimization of crystallization trials allowed the crystallization of homogeneous recombinant CS from Mycobacterium tuberculosis (MtCS). The crystals of MtCS belong to space group P6(4)22 (or P6(2)22) and diffract to 2.8 Angstrom resolution, with unit-cell parameters a = b = 129.7, c = 156.8 Angstrom. There are two molecules in the asymmetric unit. Molecular-replacement trials were not sucessful. Heavy-atom derivative screening is in progress.